Increased Risk of Acute Myocardial Infarction in Carriers of the Hemochromatosis Gene Cys282Tyr Mutation - Tomi‐Pekka Tuomainen; Kimmo Kontula; Kristiina Nyyssönen; Timo A. Lakka; Tiina Heliö; Jukka T. Salonen (1999)
Background —Homozygosity for a relatively common Cys282Tyr mutation of the human hemochromatosis-associated ( HFE ) gene was recently found to account for most cases of hereditary hemochromatosis. Because excess iron has been postulated to enhance risk of vascular disease, we studied whether occurrence of this mutation was associated with increased risk of first acute myocardial infarction in healthy middle-aged men in a prospective cohort study. Methods and Results —Study subjects were the 1150 participants in the population-based Kuopio Ischemic Heart Disease Risk Factor Study (KIHD), aged 42, 48, 54, or 60 years at baseline, who had no coronary heart disease at baseline and for whom a DNA sample was available. Information about myocardial infarctions was collected prospectively by use of FINMONICA (FINnish MONItoring of trends and determinants in CArdiovascular disease study) and hospital data. Events were classified by MONICA (MONItoring of trends and determinants in CArdiovascular disease study) diagnostic criteria. The HFE Cys282Tyr mutation was assayed by a solid-phase minisequencing technique. One subject was homozygous and 76 individuals were heterozygous for the HFE Cys282Tyr mutation (6.7%). During a mean follow-up of 9 years, 8 (10.4%) of 77 carriers and 60 (5.6%) of 1073 noncarriers experienced an acute myocardial infarction. In a Cox proportional hazards model allowing for the other strongest risk factors, the carriers had a 2.3-fold (95% CI 1.1 to 4.8; P =0.03) risk of acute myocardial infarction compared with noncarriers. Conclusions —Male carriers of the common hemochromatosis gene mutation are at 2-fold risk for first acute myocardial infarction compared with noncarriers.